Electric Characterization and Modeling of Microfluidic-Based Dye-Sensitized Solar Cell - Adriano Sacco; Andrea Lamberti; Marzia Quaglio; Stefano Bianco; Elena Tresso; Anca-Luiza Alexe-Ionescu; Candido F. Pirri (International Journal of Photoenergy)
The electric response to an external periodic voltage of small amplitude of dye-sensitized solar cells (DSCs) made up with an alternative architecture has been investigated. DSCs have been fabricated with a reversible sealing structure, based on microfluidic concepts, with a precise control on the geometric parameters of the active chamber. Cells with different electrolyte thicknesses have been characterized, without varying the thickness of the TiO2 layer, both under illumination and in dark conditions. Measurements of the electric impedance have been performed in the presence of an external bias ranging from 0 V to 0.8 V. The experimental data have been analyzed in terms of a transmission line model, with two transport channels. The results show that the photovoltaic performances of the microfluidic cell are comparable with those obtained in irreversibly sealed structures, actually demonstrating the reliability of the proposed device.